Nanoparticular inhibitors of flavivirus proteases from Zika, West Nile and Dengue virus are cell-permeable antivirals - Schroeder, Barbara; Demirel, Peter; Fischer, Christina; Masri, Enaam; Kallis, Stephanie; Redl, Lisa; Rudolf, Thomas; Bergemann, Silke; Arkona, Christoph; Nitsche, Christoph; Bartenschlager, Ralf; Rademann, Jörg (ACS medicinal chemistry letters, 2021)
Viral proteases have been established as drug targets in several viral diseases including human immunodeficiency virus and hepatitis C virus infections due to the essential role of these enzymes in virus replication. In contrast, no antiviral therapy is available to date against flaviviral infections including those by Zika virus (ZIKV), West Nile virus (WNV), or dengue virus (DENV). Numerous potent inhibitors of flaviviral proteases have been reported; however, a huge gap remains between the in vitro and intracellular activities, possibly due to low cellular uptake of the charged compounds. Here, we present an alternative, nanoparticular approach to antivirals. Conjugation of peptidomimetic inhibitors and cell-penetrating peptides to dextran yielded chemically defined nanoparticles that were potent inhibitors of flaviviral proteases. Peptide–dextran conjugates inhibited viral replication and infection in cells at nontoxic, low micromolar or even nanomolar concentrations. Thus, nanoparticular antivirals might be alternative starting points for the development of broad-spectrum antiflaviviral drugs.